Higher mortality in patients with right hemispheric intracerebral haemorrhage: INTERACT1 and 2. Issue 12 (14th January 2015) - Sato, Shoichiro; Heeley, Emma; Arima, Hisatomi; Delcourt, Candice; Hirakawa, Yoichiro; Pamidimukkala, Vijaya; Li, Zhendong; Tao, Qingling; Xu, Yuehong; Hennerici, Michael G; Robinson, Thompson; Tzourio, Christophe; et al.
Abstract : Background and purpose: Controversy exists over the prognostic significance of the affected hemisphere in stroke. We aimed to determine the relationship between laterality of acute intracerebral haemorrhage (ICH) and poor clinical outcomes. Methods: A subsidiary analysis of the INTERACT Pilot and INTERACT2 studies—randomised controlled trials of patients with spontaneous acute ICH with elevated systolic blood pressure (BP), randomly assigned to intensive (target systolic BP <140 mm Hg) or guideline-based (<180 mm Hg) BP management. Outcomes were the combined and separate end points of death and major disability (modified Rankin scale (mRS) scores of 3–6, 6 and 3–5, respectively) at 90 days. Results: A total of 2708 patients had supratentorial/hemispheric ICH and information on mRS at 90 days. Patients with right hemispheric ICH (1327, 49%) had a higher risk of death at 90 days compared to those with left hemispheric ICH after adjustment for potential confounding variables (OR, 1.77 (95% CI 1.33 to 2.37)). There were no differences between patients with right and left hemispheric ICH regarding the combined end point of death or major disability or major disability in the multivariable-adjusted models (1.07 (0.89 to 1.29) and 0.85 (0.72 to 1.01), respectively). Conclusions: Right hemispheric lesion was associated with increased risk of death in patients with acute ICH. The laterality of the ICH does not appear to affect the level of disability in survivors. Trial registration number: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00226096 and NCT00716079 .